Family context and individual situation of teens before, during and after pregnancy in Mexico City - Reyna Sámano; Hugo Martínez-Rojano; David Robichaux; Ana Lilia Rodríguez-Ventura; Bernarda Sánchez-Jiménez; Maria de la Luz Hoyuela; Estela Godínez; Selene Segovia (BMC, 2017)
Abstract Background In the last 20 years, adolescent pregnancy has become one of the most critical problems affecting women in Latin America and the Caribbean. Methods This qualitative study was based on in-depth interviews with 29 teen mothers. All of the pregnant teens were from low- to lower-middle-class social strata in the Mexico City metropolitan area. The family (living with the girl) and the individual context of pregnant teens were analysed on the basis of data from at least three interviews: during pregnancy and at approximately 6 and 24 months following delivery. Additionally, six mothers, four fathers, and four partners of the pregnant girls of the group were interviewed. The information on the individual and family situation before, during and after the pregnancy was recorded and transcribed, then analysed in three phases, comprising pre-analysis, exploration and interpretation. Results The pregnant teens had a family background of teen pregnancy. The girls disclosed feelings of repression, loneliness and indifference to their parents, leading them to unprotected sexual relations without fear of pregnancy. After the pregnancy, communication improved between the girls and their parents, but became worse with their partner. Consequently, these teens returned to feeling as they did before getting pregnant. They stated that they would make their situation work for the sake of their child, and regretted dropping out of school and getting pregnant so young. Almost all said they were seeking love outside the family, which revealed a scenario of limited communication and unsatisfactory relations within the family. Conclusions Understanding how communication works between parents and children is necessary to avoid teenage pregnancy, as well as early marriage or cohabitation, resulting in dropping out of school and financial constraints, which lead to great frustrations between the couple and affects the child. In addition, it is vitally important that adolescents be motivated in the family setting in order for them to continue their studies. There is also an urgent need to implement measures that compensate for educational inequality, as well as to strengthen strategies aimed at adolescent mothers and pregnant teens that encourage their school performance through the support of scholarship programs and day care centres. Many of the problems inherent in adolescence are related to the lack of affection and support, and in many cases are a reaction to authoritarian rules or limits established unilaterally by parents with little or no dialogue involved.